Q. 39


Using factorizat

Answer :


6y 2 - y - 2 = 0
6y 2 – 4y + 3y - 2 = 0
2y(3y – 2) + (3y – 2) = 0
(2y + 1)(3y – 2) = 0
2y + 1 = 0 or 3y – 2 = 0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Draw the graph ofNCERT - Mathematics